The uses and gratifications of social media and their impact on social relationships and psychological well-being - Bhatiasevi, Veera (Frontiers in Psychiatry, 2024)
This study aims to find the antecedents that lead to the adoption of social media among adults and older adults in Thailand and the impact it has on their social relationships and psychological wellbeing. It puts forward the uses and gratifications theory focusing on purposive value, selfdiscovery, entertainment value, social enhancement, and maintaining interpersonal connectivity.Among the 1,176 participants in this study, purposive value, entertainment value, social enhancement, and maintaining interpersonal connectivity had a positive relationship with social media usage, while self-discovery showed a negative relationship. Social media use seemed to positively effect both the social relationships and psychological well-being of their users. The discussions and conclusions included here describe how this occurs, as well as the academic and practical implications that follow from them.